Metacognitive Therapy for Alcohol Use Disorder: A Systematic Case Series - Caselli, Gabriele; Martino, Francesca; Spada, Marcantonio M.; Wells, Adrian (Frontiers in Psychology, 2018)
Alcohol Use Disorder (AUD) is a debilitating condition with serious adverse effects on health and psycho-social functioning. The most effective psychological treatments for AUD show moderate efficacy, and return to dysregulated alcohol use after treatment is still common. The aim of the the present study was to undertake a preliminary investigation of the effects associated with Metacognitive Therapy (MCT) applied to DSM-5 diagnosed AUD. Four consecutively referred patients were treated using a non-cuncurrent multiple baseline design with 3- and 6-months follow-up. Each patient received twelve one hour sessions of MCT. Following MCT all patients demonstrated large and clinically meaningful reductions in weekly alcohol use and number of binge drinking episodes that were upheld at follow-up in almost all cases. Substantial changes were also observed in metacognitive beliefs as secondary outcome. Overall, this case series provides preliminary evidence that MCT can be applied to the treatment of AUD and supports a move towards funding a more definitive trial of MCT in addictive behaviours.